Imatinib reduces proliferation of leukemic cells in vitro - Alanazi, Naif Abdulla; Alanazi, Naif Enad; Alanazi, Faisal Farhan J; Altamimi, Saud; Alghamdi, Osama S; Alanazi, Abdulrahman; Shahrani, Mohamed Al; Rabea, Mohamed W Al; Arshad, Arfan; Alenzi, Faris Q (Bangladesh Journal of Medical Science, 2017)
Introduction: Philadelphia chromosome is a cytogenetic marker for chronic myeloid leukemia (CML). The main aims of this study were to assess the positive responses, side-effects and survival of CML patients treated with imatinib mesylate. Methods: All recently diagnosed CML patients who were treated with imatinib were recruited to this study. We investigated hematological and cytogenetic parameters by CBC, FISH and RT-PCR individually. Results: Of the 10 cases, 7 (70%) were males and 3 (30%) were female. Four (40%) of the cases were analyzed retrospectively and 8 cases (80%) exhibited general exhaustion (75%), fever (80%), and splenomegaly (80%). Indications of bleeding and rashes were rarely seen at presentation. The majority of the patients had a generally low risk profile (70%), 30% had intermediate risk; with no subjects exhibiting high risk CML, 9 subjects (90%) were in remission. One patient (10%) had been in remission for 3 years, 4 (40%) had been in remission for 6 years, one was in remission after 7 years and 5 (50%) were in remission after 10 years. Most of the patients (90%) exhibited a deficient major molecular reaction, after 6 years of treatment and 42% of them had a deficient major molecular reaction after 10 years of treatment. No significant side effects associated with Imatinib treatment were reported by the patients. Imatinib treatment resulted in diminished expansion in CML CFU-GM cells. Conclusion: Imatinib mesylate is indicated for the treatment of Philadelphia chromosome-positive CP-CML with no significant adverse outcomes. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.320-324